Study on bio-inspired feet based on the cushioning and shock absorption characteristics of the ostrich foot - Han, Dianlei (PLoS One, 2020)
As the main actuator of high-speed running, the ostrich feet are highly capable of cushioning and shock absorption. In this study, based on the elastic modulus scales and assembly order of the 3rd toe soft tissues and the functions of the metatarsophalangeal (MTP) joint, we designed fourteen bio-inspired feet. The impact process on loose sand was simulated on the finite element software Abaqus. Also the stress distributions and deformations of each component of the bio-inspired feet were clarified. With the peak acceleration as the index, the cushioning performances of the bio-inspired feet were compared on both loose sand and solid ground through height-variable impact tests. The 15-15-15 HA (hardness unit) bio-inspired foot showed lower peak acceleration and thereby better cushioning performance, but larger deformation, less-uniform stress distribution and thereby lower stability than the 15-35-55 HA bio-inspired foot. In fact, the silicon rubbers with different hardness degrees (which simulate the elasticity modulus scales of the digital cushions, fascia and skin) and the spring mechanism (which simulates the functions of the MTP joint) work as an “integrated system” of cushioning and shock absorption.